Loan-and-Savings Instruments for Increasing National Welfare in the Russian Empire in the 1870-1880s - Lachaeva, Marina Yu (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The author examines the ideological, target and practical aspects of the purpose of credit cooperation, as well as the activities of its organizers and participants in the fight against poverty and increasing national welfare in the 1870-1880s. This study is in the context of the involvement of Russian peasants in new economic relations during the reforms and in the post-reform period. In their text, the author reveals the role of V.N. Khitrovo, the official for special missions of the Ministry of Finance in the organization and activities of loanandsavings partnerships, when headed the St. Petersburg branch of the Committee on rural loan-and-savings and industrial partnerships under the Imperial Moscow Society of Agriculture across a significant period of time. The author analyzes the process of overcoming the class character of lending to villages, and the main areas of work in this direction by V.N. Khitrovo and his associates in the St. Petersburg branch of the Committee. The author provided information on the organizing role of the Committee during the period of V.N. Khitrovo’s secretarial duties in it from 1871 to 1890 and in the formation and strengthening of credit cooperation, a new phenomenon in the socioeconomic life of Russia.